2016
DOI: 10.1177/0263775816649183
|View full text |Cite
|
Sign up to set email alerts
|

Provocation: Technology, resistance and surveillance in public space

Abstract: Abstract. The introduction of technologies that monitor and track individuals to attribute suspicion and guilt has become commonplace in practices of order maintenance in public space. A case study of the introduction of a marker spray in Dutch urban public transport is used to conceptualise the role of technology in everyday resistances against surveillance. The introduction of this technology made available alternative subject positions. The notion of provocation is proposed for the opening up of social spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Such a conceptualisation of resistance starts with problematising dominant interpretations of Foucault's (1978) analysis of power and resistance, which assume the existence of a merely coercive power and treat resistance as a mere reaction to it. Such an approach to power and resistance has shaped our understanding of conflict in urban space: see, for example, Ju and Tang (2010) on grassroots environmental groups against the South Korea government, Lauermann and Vogelpohl (2019) on protest campaigns against the organisation of megaevents in Boston and Hamburg, Davies and Blanco (2017) on contentious anti-austerity politics, Pearsall (2013) on anti-gentrification struggles in New York, or work describing different modes of resistance to surveillance (Gromme´, 2016;Swanlund and Schuurman, 2019). Although this work is important and, indeed, necessary for understanding and visualising oppositional politics, it has also been problematised because it 'draws a strict contrast between the diabolic world of power and the liberating world of resistance' (Fleming and Spicer, 2008: 304).…”
Section: The Primacy Of Resistance In Urban Spacementioning
confidence: 99%
“…Such a conceptualisation of resistance starts with problematising dominant interpretations of Foucault's (1978) analysis of power and resistance, which assume the existence of a merely coercive power and treat resistance as a mere reaction to it. Such an approach to power and resistance has shaped our understanding of conflict in urban space: see, for example, Ju and Tang (2010) on grassroots environmental groups against the South Korea government, Lauermann and Vogelpohl (2019) on protest campaigns against the organisation of megaevents in Boston and Hamburg, Davies and Blanco (2017) on contentious anti-austerity politics, Pearsall (2013) on anti-gentrification struggles in New York, or work describing different modes of resistance to surveillance (Gromme´, 2016;Swanlund and Schuurman, 2019). Although this work is important and, indeed, necessary for understanding and visualising oppositional politics, it has also been problematised because it 'draws a strict contrast between the diabolic world of power and the liberating world of resistance' (Fleming and Spicer, 2008: 304).…”
Section: The Primacy Of Resistance In Urban Spacementioning
confidence: 99%
“…These provocations served as provotypes (provocative prototypes, a prevalent method in design research) to provide space to create meaning in an emergent context and then to connect that meaning to cultural values (River and Mactavish 2017) around teaching. These provotypes begin to capture how technologies 'open up social spaces' (Gromme 2016(Gromme : 1008) by making available space to respond with alternatives.…”
Section: Studying the Futurementioning
confidence: 99%
“…Intersecting STS with law and philosophy (Hildebrandt and Rouvroy 2011), communication and media studies (Gillespie 2014), surveillance studies (Kroener and Neyland 2012), and Human Computer-Interaction studies (Suchman 2007), they have successfully shown how the study of algorithms, autonomic computing, software and technological change can provide an entry-point to study power, agency, accountability and human autonomy. In security studies too, it has been shown that the deployment of algorithmic techniques for security entails important political and ethical stakes that should be described and analysed (Amoore and Raley 2017;Aradau and Blanke 2015;Grommé 2016;Kaufmann et al 2019). But digital security technologies may be hard to comprehend.…”
Section: Secrecy and Digital Security Technologiesmentioning
confidence: 99%